Lucy's back: Reassessment of fossils associated with the A.L. 288-1 vertebral column. Issue 85 (August 2015) - Meyer, Marc R.; Williams, Scott A.; Smith, Michael P.; Sawyer, Gary J.
Abstract: The Australopithecus afarensis partial skeleton A.L. 288-1, popularly known as "Lucy" is associated with nine vertebrae. The vertebrae were given provisional level assignments to locations within the vertebral column by their discoverers and later workers. The continuity of the thoracic series differs in these assessments, which has implications for functional interpretations and comparative studies with other fossil hominins. Johanson and colleagues described one vertebral element (A.L. 288-1am) as uniquely worn amongst the A.L. 288-1 fossil assemblage, a condition unobservable on casts of the fossils. Here, we reassess the species attribution and serial position of this vertebral fragment and other vertebrae in the A.L. 288-1 series. When compared to the other vertebrae, A.L. 288-1am falls well below the expected size within a given spinal column. Furthermore, we demonstrate this vertebra exhibits non-metric characters absent in hominoids but common in large-bodied papionins. Quantitative analyses situate this vertebra within the genus Theropithecus, which today is solely represented by the gelada baboon but was the most abundant cercopithecoid in the KH-1s deposit at Hadar where Lucy was discovered. Our additional analyses confirm that the remainder of the A.L. 288-1 vertebral material belongs to A. afarensis, and we provide new level assignments for some of the other vertebrae, resulting in a continuous articular series of thoracic vertebrae, from T6 to T11. This work does not refute previous work on Lucy or its importance for human evolution, but rather highlights the importance of studying original fossils, as well as the efficacy of the scientific method.